Simvastatin-Encapsulated Topical Liposomal Gel for Augmented Wound Healing: Optimization Using the Box-Behnken Model, Evaluations, and In Vivo Studies - Mohamed Rahamathulla; Rahul Pokale; Yousef Al-ebini; Riyaz Ali M. Osmani; Kamal Y. Thajudeen; Ravi Gundawar; Mohammed Muqtader Ahmed; Syeda Ayesha Farhana; Thippeswamy Boreddy Shivanandappa (MDPI AG, 2024)
Statins function beyond regulating cholesterol and, when administered systemically, can promote wound healing. However, studies have yet to explore the topical use of statins for wound healing. The present study demonstrated the topical administration of SIM and aimed to formulate, evaluate, and optimize Simvastatin (SIM)-encapsulated liposome gel carrier systems to facilitate successful topical wound healing. Liposomes containing SIM were formulated and optimized via a response surface methodology (RSM) using the thin-film hydration method. The effects of formulation variables, including the 1,2-dioleoyloxy-3-trimethylammoniumpropan (DOTAP) concentration, Span 80 concentration, and cholesterol concentration, on zeta potential (mV), entrapment efficacy (%), and particle size (nm) were studied. The optimized liposome formulation (F-07) exhibited a zeta potential value of 16.56 ± 2.51 mV, revealing robust stability and a high SIM encapsulation efficiency of 95.6 ± 4.2%, whereas its particle size of 190.3 ± 3.3 nm confirmed its stability and structural integrity. The optimized liposome gel demonstrated pseudoplastic flow behavior. This property is advantageous in topical drug delivery systems because of its ease of application, improved spreadability, and enhanced penetration, demonstrating prolonged SIM release. The assessment of the wound healing efficacy of the optimized liposomal gel formulation demonstrated a substantial decrease in wound size in mice on the sixteenth day post-wounding. These findings suggest that the use of liposomal gels is a potential drug delivery strategy for incorporating SIM, thereby augmenting its effectiveness in promoting wound healing.